Deducing neighborhoods of classes from a fitted model - Alexander Gerharz; Andreas Groll; Gunther Schauberger (AStA Advances in Statistical Analysis, 2024)
In this article, a new kind of interpretable machine learning method is presented, which can help to understand the partition of the feature space into predicted classes in a classification model using quantile shifts, and this way make the underlying statistical or machine learning model more trustworthy. Basically, real data points (or specific points of interest) are used and the changes of the prediction after slightly raising or decreasing specific features are observed. By comparing the predictions before and after the shifts, under certain conditions the observed changes in the predictions can be interpreted as neighborhoods of the classes with regard to the shifted features. Chord~diagrams are used to visualize the observed changes. For illustration, this quantile shift method (QSM) is applied to an artificial example with medical labels and a real data example.
Keywords: 510; Interpretable machine learning; Explainable artificial intelligence; Classification task; Feature space partition; Chord~diagrams